2019
DOI: 10.1038/s41372-019-0451-5
|View full text |Cite
|
Sign up to set email alerts
|

Infant mortality: the contribution of genetic disorders

Abstract: Objective-To determine the proportion of infant deaths occurring in the setting of a confirmed genetic disorder.Study Design-A retrospective analysis of the electronic medical records of infants born from January 1, 2011 to June 1, 2017 who died prior to one year of age.Results-573 deceased infants were identified. 117 were confirmed to have a molecular or cytogenetic diagnosis in a clinical diagnostic laboratory and an additional 7 were diagnosed by research testing for a total of 124/573 (22%) diagnosed infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 32 publications
0
45
0
1
Order By: Relevance
“…Informed consent was obtained via our Institutional Review Board-approved protocol. Trio exome sequencing was performed through the Broad Institute Center for Mendelian Genomics using methods as previously described (Wojcik et al 2019).…”
Section: Examples Of Monogenic Cause Of Congenital Anomalies From Ourmentioning
confidence: 99%
“…Informed consent was obtained via our Institutional Review Board-approved protocol. Trio exome sequencing was performed through the Broad Institute Center for Mendelian Genomics using methods as previously described (Wojcik et al 2019).…”
Section: Examples Of Monogenic Cause Of Congenital Anomalies From Ourmentioning
confidence: 99%
“…Little, however, has yet been published with regard to the contribution of genetic diseases to infant mortality using this technology. In six published studies and the cohort reported herein a weighted average of 21% of infant deaths was attributable to single locus genetic diseases 25 , 28 , 45 , 63 65 . However, the range of attribution varied widely between studies (6%-86%), reflecting different experimental designs and inclusion and exclusion criteria.…”
Section: Discussionmentioning
confidence: 91%
“…In two studies, genome sequencing was performed post mortem 63 , 64 . One study had both ante and post mortem genomic sequencing 65 . While all included inpatient and community deaths, the inclusion criteria differed in each study (Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Congenital anomalies and genetic conditions are noted in approximately 2–5% of pregnancies and are major causes of fetal demise and infant death. 1 , 2 Chromosomal microarray is recommended to evaluate for chromosomal abnormalities in fetuses with congenital anomalies, but 60–70% of fetuses remain without a genetic diagnosis after microarray, which can complicate counseling, prenatal management, and parental decision-making. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%